Transcutaneous tibial nerve stimulation versus parasacral stimulation in the treatment of overactive bladder in elderly people: a triple-blinded randomized controlled trial (Clinics, 2020)
OBJECTIVES: To evaluate the effect of transcutaneous tibial nerve stimulation (TTNS) and transcutaneous parasacral stimulation on the treatment of overactive bladder (OAB) in elderly people and to compare the final results between groups. METHODS: Fifty female volunteers, mean age 68.62 (±5.9) years, were randomly allocated into two groups: those receiving TTNS (G1, N=25) and those receiving transcutaneous parasacral stimulation (G2, N=25). The primary outcome was the International Consultation on Incontinence Questionnaire (ICIQ-OAB) score, and secondary outcomes were the International Consultation on Incontinence Questionnaire – short form (ICIQ-SF) score and 3-day bladder diary measurements. Volunteers were assessed before and after the treatment. Clinical Trials (ReBeC): RBR-9Q7J7Y. RESULTS: Both groups’ symptoms improved as measured by the ICIQ-OAB (G1 = o0.001; G2 = o0.001) and ICIQSF (G1 = o0.001; G2 = o0.001). In the 3-day bladder diary assessments after treatment, G1 showed a reduced number of nocturia (po0.001), urgency (po0.001) and urge urinary incontinence episodes (po0.001), whereas G2 showed only a reduced number of nocturia episodes (po0.001). No difference between groups was found. CONCLUSION: Both of the proposed treatments were effective in the improvement of OAB symptoms, but TTNS showed a reduction in a greater number of symptoms as measured by the 3-day bladder diary. No differences were found between groups.